Design of Portable Automatic Weather Station Based on Raspberry PI - Larangga Herdianzenda; Diky Siswanto; Istiadi Istiadi (Widyagama University of Malang, 2021)
Observation of the weather elements is very necessary for the welfare of mankind, the weather elements that are observed will be used as material to predict the weather in the future. Weather data can also be used to reduce the risk of adverse effects caused by the weather itself. To measure the weather with an automated monitoring system that is cheaper and of good quality, AWS was created. The AWS design using Raspberry Pi was made as a use of Raspberry Pi mini computer technology for the purposes of the Meteorology, Climatology and Geophysics Agency (BMKG). humidity, Rain Counter, wind direction, wind speed, air pressure, altitude, and GPS. Display data can be monitored via the web in the form of an Analog Gauge.